2023
DOI: 10.1037/cdp0000497
|View full text |Cite
|
Sign up to set email alerts
|

“Talk to me”: Parent–teacher background similarity, communication quality, and barriers to school-based engagement among ethnoculturally diverse Head Start families.

Abstract: Objective: Primary caregivers (e.g., parents, grandparents, other family members) from low-income and ethnically minoritized families tend to face a host of barriers when participating in their children's school activities. Research suggests that demographic match and quality communication between caregivers and teachers could support minoritized families' school-based engagement. This study examined the associations among caregiver-teacher demographic match, caregivers' perceived communication quality with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This finding is inconsistent with the extensive evidence that bilingual education supports stronger child-level outcomes for DLLs. It is also inconsistent with recent evidence showing that language match, per se, led to fewer perceived barriers to home-school engagement among caregivers from culturally and linguistically diverse families (Li et al, 2021). However, Cook et al (2023) showed that language match is a complex variable, as children are unlikely to be randomly assigned to a language match condition.…”
Section: Interpreting Childcare Setting and Language Match Resultsmentioning
confidence: 79%
“…This finding is inconsistent with the extensive evidence that bilingual education supports stronger child-level outcomes for DLLs. It is also inconsistent with recent evidence showing that language match, per se, led to fewer perceived barriers to home-school engagement among caregivers from culturally and linguistically diverse families (Li et al, 2021). However, Cook et al (2023) showed that language match is a complex variable, as children are unlikely to be randomly assigned to a language match condition.…”
Section: Interpreting Childcare Setting and Language Match Resultsmentioning
confidence: 79%
“…This suggests that families frequently engage in communication with their children's teachers, providing substantial support for their academic concerns. Li et al (2021) highlighted that parents and family members, serving as primary caregivers, often encounter obstacles when engaging in conversations with teachers, especially within low-income and ethnic minority households. Parents from low-income households may find it difficult to follow up on their children's academic progress as they are busy working to provide for their families.…”
Section: Results Andmentioning
confidence: 99%
“…Communication between teachers and parents may be particularly important for DLLs who are simultaneously developing their first language (L1) and their second language (L2) (Gutiérrez et al, 2010), and whose families often face barriers to engaging in ECEC settings (Li et al, 2023). Forming collaborative relationships between teachers and parents of DLLs can link parents' linguistic and cultural expertise with teachers' needs for instructional supports, and teachers can share instructional strategies that in turn support children's school readiness (Sawyer et al, 2017).…”
Section: Teacher-parent Collaboration To Support Language Developmentmentioning
confidence: 99%
“…Challenges in the collaboration between teachers and parents can include childrearing disagreements and undermining (Lang et al, 2016), as well as linguistic and cultural differences and asymmetrical power relations (Aghallaj et al, 2020;Norheim and Moser, 2020;Li et al, 2023), as expressed by both parents and ECEC professionals. International studies have indicated that even though ECEC professionals expressed positive attitudes towards parent collaboration and cultural diversity, they reported less support for promoting multilingualism, which might not correspond with the language beliefs of many multilingual families (Slot et al, 2018;Aghallaj et al, 2020;Norheim and Moser, 2020).…”
Section: Challenges In Teacher-parent Collaborationmentioning
confidence: 99%
See 1 more Smart Citation